A First principles investigation for structural and optoelectronic properties of oxygen functionalized ScBiS3 monolayer - Desai, Riddhi; Naik, Yashasvi; Parmar, P. R.; Thakor, P. B. (Interactions (Cham, Switzerland), 2024)
In the present research work, structural, electronic, and optical properties of oxygen functionalized 2D ScBiS 3 monolayer have been carried out by using the first principles calculations. Both SBiS 3 O (single side functionalization) and ScBiS 3 O 2 (double side functionalization) monolayer have stable hexagonal structure. The ScBiS 3 monolayer has indirect bandgap of 1.95 eV. The oxygen functionalization on the ScBiS 3 monolayer reduce the electronic bandgap remarkably. The ScBiS 3 O and ScBiS 3 O 2 monolayers possess electronic bandgap of 1.075 eV and 0.32 eV respectively. The monolayer ScBiS 3 with and without oxygen functionalization shows optical absorption in the visible and ultraviolet region, which suggest its potential application in nanoscale optoelectronic devices.